Investigation on the female initiation practice, chinamwali/ chinamwari in Chewa communities: a case of Chegutu urban 2000 -2016 - Gondo, Tracey (Midlands State University, 2018)
Female initiation practice (Chinamwali/ Chinamwari) is a traditional culture practiced by the Chewa speaking people. The study investigates the background of the practice, location of the study, description of the group, the changes it has undergone and reasons behind these changes. The study reveals that the practice involves teachings on menstruation, life skills and sex education in order to mould an ideal woman. The age group of initiates, duration of seclusion, ritual baths and shaving of initiates are changing gradually due to continuous criticism from Christianity, modernisation and women and children’s rights awareness campaigns. The changes however serve to encourage its continuity in the modern day society and it is celebrated for its ability to curb promiscuity and the fear of the spread of HIV/AIDS. The study looked on how the practice affects the right of girls to education and sexual reproductive health and its link to the school drop outs, early marriages and child prostitution and how it link with education since this area is usually ignored by many scholars as much focus is placed on differences and weaknesses of the practice and sometimes scholars tend to take sides on whether the practice is good or bad. To come up with this piece of work the researcher used individual and group interviews, focus group discussions, reports from clubs and organisations, debates, participant observation and written sources which included internet sources and published books and journals to supplement information obtained from primary sources. Targeted population for interviews were initiators (Nyamukungu), initiates, Faith Based Organisation (FBOs), teenage girls, gender focal persons, Child Care Workers.